Psychiatric and neuropsychological issues in sports medicine - Esfandiari, A.; Broshek, D. K.; Freeman, J. R. (Clinics in Sports Medicine, 2011)
This article reviews psychiatric/psychological issues in the athletic training room, including recognition of these issues and a framework for management. Because the majority of research has been conducted in college settings, most of the issues discussed are presented in the context of college sports, although the results generalize to other athletic arenas. Greater awareness of psychological issues, empirical research, and education about mental health issues in the sports medicine community are clearly needed.